Innovation Performance and Government Financing - Roger Svensson (Research Institute of Industrial Economics (IFN), 2006)
External financing is important when inventors and small technology-based firms wish to commercialize their inventions. However, it is likely that problems related to adverse selection and moral hazard are present, and market failures occur, since inventors know more about the inventions than do potential external financiers. To overcome these problems, the Swedish Government has intervened in the market by offering loans with different terms to firms and inventors. Using a unique database on Swedish patents owned by individuals and small firms, this paper analyzes how different forms of external financing influence the outcome when patents are commercialized. The estimations show that projects with soft government financing in the R&D-phase have a significantly worse performance than projects without such financing, whereas projects with more market-oriented government loans perform as the average. Distinguishing between governmental financing alternatives with different terms makes it possible to draw the conclusion that government failure primarily depends on bad financing terms, rather than bad choices of projects. A policy implication is therefore that government institutions should make their loans more market-oriented already in the R&D-phase.
Keywords: G30; O31; O38; 330; Patents; Commercialization; Innovations; Outcome; External Financing; Government Intervention; Betriebliche Forschung; Patent; Risikokapital; Innovationspolitik; Erfolgsfaktor; Schweden